2013
DOI: 10.1016/j.cell.2012.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Latent Enhancers Activated by Stimulation in Differentiated Cells

Abstract: According to current models, once the cell has reached terminal differentiation, the enhancer repertoire is completely established and maintained by cooperatively acting lineage-specific transcription factors (TFs). TFs activated by extracellular stimuli operate within this predetermined repertoire, landing close to where master regulators are constitutively bound. Here, we describe latent enhancers, defined as regions of the genome that in terminally differentiated cells are unbound by TFs and lack the histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
876
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 717 publications
(962 citation statements)
references
References 79 publications
62
876
4
3
Order By: Relevance
“…Therefore, it is not surprising that the main consequence of the ectopic expression of ZEB1 differs greatly between cancer cell types. This is because transcription factor binding regions are affected by the epigenetic environment in the cells, which is dynamically regulated by TGF‐β and other extracellular stimuli (Ostuni et al ., 2013). The observation that ZEB1 has differential effects on the expression of genes that are either downregulated or upregulated by TGF‐β in MDA‐231‐D cells also supports the importance of cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that the main consequence of the ectopic expression of ZEB1 differs greatly between cancer cell types. This is because transcription factor binding regions are affected by the epigenetic environment in the cells, which is dynamically regulated by TGF‐β and other extracellular stimuli (Ostuni et al ., 2013). The observation that ZEB1 has differential effects on the expression of genes that are either downregulated or upregulated by TGF‐β in MDA‐231‐D cells also supports the importance of cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatin status of the seven IRF-containing binding schemes was examined for K4me1 (a mark of enhancer regions) and H3K27Ac (transcriptional activity) and for open chromatin conformation as determined by formaldehydeassisted isolation of regulatory elements (FAI REs; Figs. 2 B and S2; Ostuni et al, 2013). Distinctively, only clusters 1, 3, and 5 show characteristics of active regulatory regions before IFN-γ treatment with open chromatin and monomethylated H3K4, with an increase of H3K27 acetylation at clusters 1 and 5 sites 3 h after IFN-γ stimulation (Fig.…”
Section: Irf8 and Irf1 Genomic Binding Schemes And Associated Chromatmentioning
confidence: 99%
“…Genes showing significantly reduced IFN-γ-dependent activation (more than or equal to twofold; n = 204) in ei- Clustering analysis of the 21,248 unique IRF1-and/or IRF8-containing regulatory regions (including STAT1 and PU.1) before or after IFN-γ treatment. Each horizontal line presents the read density in a ±1-kb region around a unique position; DNA accessibility (FAI RE; Ostuni et al, 2013) and H3K4me1 and H3K27Ac epigenetic datasets are shown for a ±2-kb region surrounding the cluster peaks. Different binding combinations before or after IFN-γ treatment are shown (clusters numbered 1-7).…”
Section: Regulation Of Ifn-γ-induced Expression Of Target Genes By Irmentioning
confidence: 99%
“…Notably, H3K4me1 was absent at distal enhancers both before and early after stimulation (6 h), while it increased by 5-to 25-fold (depending on the region) at 20 h (Fig. 5e), thus indicating the emergence of latent or de novo enhancers 31 . By contrast, high levels of H3K4me1 were found already present at the same regions in unstimulated monocytes, and remained unchanged after cell activation (Fig.…”
mentioning
confidence: 99%